Comparison of Field and Laboratory Soil Stability Values on the Soko - Tuban Road - Mohammad Zainul Ikhwan; Toni Budi Santoso (Electronic Journal of Education, Social Economics and Technology, 2025)
The good Soko-Tuban road experienced damage that distrupted comfort. The results showed that the test soil included organic clay with an average density of 2.33 gr/cm³ and a water ontent of 43.19%. The liquid limit value was 77.33%, the plastic limit was 32.7%, and the plasticity index was 44.63%. DCP testing was carried out on two samples with different road conditions, namely at STA 7+100 and 7+200 (good road) and STA 7+800 and 7+900 (damaged road). The CBR value at STA 7+100 on the east side was 12.09% and 7+200 on the west side was 9.87%. At STA 7+800, the CBR value on the east side was 5.23% and STA 7+900 on the west side was 10.59%. The laboratory CBR value was taken from two samples with three variations of impacts 10x, 30x, and 65x. In good road conditions at STA 7+100 the highest average CBR value is 17.12%. In damaged road conditions at STA 7+800 the average CBR value is 11.52%. The significant difference in laboratory and field CBR values is influenced by road conditions and soil characteristics.